Thistlemarsh - Corrigan, Moorea (Berkley, 2026)
"Faeries disappeared over one hundred years ago, as suddenly as slipping through a doorway. It was only the very foolish, or the very determined, who held out hope for their return. In the wake of World War I, the world is a decidedly unmagical place for Misneach "Mouse" Dunne. Mouse once dreamed of becoming a Faerie anthropologist, but with one telegram, her world shattered. At the Somme, her cousin Bertie's body disappeared into the mud, and her brother, Roger, came home with devastating shell shock. It was time, she knew, to put aside childish dreams. When Mouse receives news that her uncle, Lord Dewhurst, has left her Thistlemarsh Hall, a dilapidated manor in the English countryside, she has to return to her childhood home and claim her birthright. Thistlemarsh was blessed by the Faerie King himself before the Faeries left England for good. But there is a catch in Lord Dewhurst's offer: If Mouse does not rehabilitate the crumbling house in one month's time, she will forfeit her inheritance and any hope of caring for her brother. It quickly becomes clear it's impossible to repair the manor in the allotted time, until a mysterious Faerie appears with a proposition. He offers to restore Thistlemarsh . . . for a small price. Mouse knows better than to trust a Faerie-especially one so insufferably handsome and arrogant-but she is out of options. There are dark and magical forces at work in the house, and Mouse must confront the ghosts of her past and the secrets of her heart or lose Thistlemarsh, and herself, in the process"-- Provided by publisher.